Effects of human herpesvirus 6B reactivation on cognitive function in cord blood transplant recipients: a prospective multicenter study - Ogata, Masao; Oshima, Kumi; Takano, Kuniko; Kawano, Rie; Ueda, Yasunori; Imamura, Takashi; Nakamura, Yukinori; Okada, Takahiro; Toubai, Tomomi; Ueki, Toshimitsu; Uoshima, Nobuhiko; Ishida, Hiroyuki; et al. (International journal of hematology, 2024)
This prospective multicenter study aimed to determine the effects of human herpesvirus-6B (HHV-6B) reactivation on central nervous system (CNS) function in cord blood transplant (CBT) recipients. Our focus was to track HHV-6B reactivation and evaluate its association with delirium and cognitive function, specifically in the domains of verbal memory, attention/processing speed, and quality of life (QOL). A cohort of 38 patients participated in this study. Of the 37 patients evaluated, seven (18.9%) developed delirium, with six of these cases emerging after HHV-6B reactivation (median lag, 7 days). Evaluation of verbal memory showed that the final trial score for unrelated words at 70 days after transplantation was significantly lower than that before preconditioning ( P = 0.004) among patients ( n = 15) who experienced higher-level HHV-6B reactivation (median or higher maximum plasma HHV-6 DNA load for participating patients). Patients without higher-level reactivation did not show significant declines in verbal memory scores. QOL was assessed using the 36-item Short-Form Health Survey, and the social functioning score 1 year post-transplantation was significantly lower in patients who experienced higher-level HHV-6B reactivation than in those who did not. Our findings suggest that higher-level HHV-6B reactivation can detrimentally affect certain cognitive functions in CBT recipients.